Chikungunya virus emergence in the Americas and Europe - (:unkn) unknown (My University, 2015)
Chikungunya virus (CHIKV), transmitted mainly by the mosquitoes Aedes aegypti and Aedes albopictus, is a major public health problem. Since 2004, CHIKV epidemics have been reported in Africa, Asia, the Indian Ocean Islands, and Europe. Only the Americas seemed spared despite high densities of mosquitoes and multiple introductions of the virus to the continent by travelers returning from countries where CHIKV was circulating. We have assessed the risk of CHIKV emergence in the Americas by evaluating the vector competence of 35 local populations of Ae. aegypti and Ae. albopictus infected with different strains of CHIKV. These populations were shown to be susceptible to CHIKV infection, highlighting the predominant role of salivary glands as a "filter" of transmission. Genotyping of Ae. albopictus from the Americas using microsatellites allowed the identification of a genetic cluster of populations characterized by a low transmission of CHIKV strains of the East-Central-South-African genotype. In October 2013, Asian strains of CHIKV began circulating in the Caribbean. Thus, we evaluated the susceptibility of 11 populations of Ae. aegypti and Ae. albopictus to the Asian CHIKV genotype and showed that the two species were sufficiently competent to ensure dissemination of the virus throughout the continent. Furthermore, we showed that Ae. albopictus was likely to facilitate the spread of CHIKV to Europe. However, the vector competence of French Ae. albopictus to the Asian CHIKV genotype was negatively affected by temperatures lower than those usually found in tropical countries.
Keywords: African Research